ATTITUDE TOWARDS PHYSICAL EDUCATION COURSES AND ACADEMIC PERFORMANCE OF SOPHOMORE STUDENTS IN A STATE UNIVERSITY - Panganiban, Teejay D; Chavez, Nicole I; Delizo, Jeffrey L; Recinto, Neil Jose Aloysius B (PUPIL: International Journal of Teaching, Education and Learning, 2019)
The purpose of this study was to ascertain the attitude and academic performance in Physical Education courses of sophomore students in the College of Teacher Education at Batangas State University- JPLPC Campus, for the academic year 2013- 2014. It sought to investigate further the following main problems: What is the attitude of the student towards Physical Education courses in terms of movement, fitness management, safety, personal and social management and healthy lifestyle practices? How may the academic performance of the respondents be described? Is there a significant relationship between the attitude of the respondents and their academic performance in Physical Education? What is the implication of the findings of this study to Physical Education instruction?This study was guided by the null hypothesis which stated that there was no significant relationship between the attitudes of the respondents in terms of movement, fitness management, personal and social management and healthy lifestyle practices, and their academic performance in Physical Education.The researchers applied the descriptive correlational method of research. The principal tool in gathering the data was the questionnaire prepared by the researchers. The study employed the frequency and percentage, weighted mean, Pearson’s r and Chi Square formula.After the careful tabulation, statistical treatment, analysis and interpretation of data, the following findings are revealed: the composite mean of 3.28, 3.43, 3.49, 3.25, 3.32 reflects a highly positive attitude among the respondents in terms of Movement, Fitness Management, Safety, Personal and Social Management, and Healthy and Lifestyle Practices respectively.Considering the significant findings revealed and conclusions drawn in this study, the researchers suggested the following recommendations: Enrichment activities were suggested to improve the attitude of the respondents in the areas of Physical Education Movement, Fitness Management, Safety, Personal and Social Management and Healthy Lifestyle Practices.